THE INFLUENCE OF TANGIBLE REWARDS TO STUDENT’S MOTIVATION IN 4TH GRADE SDN SINARGALIH 1 CIRANJANG STUDENTS - Tedi Cahya; Anggraeni Novianti Kusnadi; Anita Anggraeni (PROJECT (Professional Journal of English Education), 2018)
This study focused on the influence of tangible rewards to students’ motivation on the learning process. The objective of this research is to describe how tangible reward can improve students’ motivation. This research used descriptive qualitative as a research design. The data of this research were obtained from interview to the teacher who teaches in 4th-grade students’ of SDN Sinargalih 1 Ciranjang. The interview was conducted twice. The result of the research would be described in the form of words. The result of the interview, the teacher had tried to apply tangible reward to improve students’ motivation. The teacher was quite good when used the tangible reward to improve the students’ motivation. Meanwhile, the result from teacher interview also showed that the students’ had better motivation from the first meeting to the next meeting. They tried to more active in the process of learning, although some of the students’ are still passive and had less of motivation. Then the result of an interview given to the teacher showed a positive effect. Tangible reward made the students participate actively. It is viewed by the students when the teacher gives some tests to get the reward. The students try to answer teacher question and had no fear to make mistakes.